Effect of Parity and Stage of Gestation on Growth and Feed Efficiency of Gestating Sows - L. L. Thomas; R. D. Goodband; M. D. Tokach; J. C. Woodworth; J. M. DeRouchey; S. S. Dritz (Kansas Agricultural Experiment Station Research Reports, 2017)
The effects of parity and stage of gestation on female growth criteria and reproductive performance were evaluated at a commercial sow farm. A total of 712 females (Camborough, PIC, Hendersonville, TN) were group-housed and individually fed with electronic sow feeders. Gilts (parity 1) and sows were offered 4.4 and 5.0 lb of feed per day (4.7 and 5.3 Mcal NE per d), respectively. Females were moved from the breeding stall to pens on d 5 of gestation. A scale was located in the alleyway to weigh sows as they left individual feeding stations. Feed intake and BW were recorded daily throughout gestation, generating values for ADFI, ADG, and G:F for each sow. Data were divided into 3 parity groups: 1, 2, and 3+, and gestation was divided into 3 periods: d 5 to 39, 40 to 74, and 75 to 109. From d 5 to 39, ADFI was decreased (P<0.05) for parity 3+ sows compared to the other periods of gestation. Parity 2 sows, although provided the same feed allowance, had greater (P<0.05) ADFI during the first period of gestation than parity 3+ sows. Parity 1 and 2 sow ADG increased (P<0.05) from d 39 to 74 of gestation, then decreased (P<0.05) from d 74 to 109 of gestation. Parity 3+ sow ADG increased (P<0.05) in each subsequent period of gestation. Parity 1 sows had the greatest (P<0.05) ADG in comparison to parity 2 and 3+ sows in each period of gestation. Regardless of parity group, G:F was poorest (P<0.05) from d 5 to 39 of gestation compared with sequential periods of gestation. Parity 1 sow G:F was greater (P<0.05) than parity 2 and 3+ sows for all periods of gestation. Backfat gain indicated that parity 1 sows maintained backfat (approximately 0.7 in.) while parity 2 and 3+ sows gained (P<0.05) approximately 0.04 in. backfat throughout gestation. Total born was greatest (P<0.05) for parity 3+ sows with parity 1 sows marginally greater (P<0.10) than parity 2 sows. Although there was evidence (P<0.001) for positive correlations between BW gain and total born in parities 1 (r = 0.23; P =<0.001), 2 (r = 0.15; P = 0.035), and 3+ (r = 0.29; P<0.001), these correlations were considered weak. Overall, this study indicates that parity 1 sows have the best feed efficiency in gestation and lack strong correlations between feed intake or growth and reproductive performance.
Keywords: electronic sow feeder; feed efficiency; gestation; sows